2016
DOI: 10.1002/alr.21817
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic characterization of the retroantral ethmoid cell

Abstract: Background The retroantral ethmoid cell (RAEC) is defined as a posterior ethmoid cell that pneumatizes inferolaterally behind the posterior wall of the maxillary sinus. The RAEC can present a challenge to otolaryngologists during endoscopic ethmoidectomy due to its concealed location. It is also encountered during the endoscopic transpterygoid approach to the skull base, which requires dissection behind the posterior wall of the maxillary sinus. Because the RAEC is not described in the literature, this study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 8 publications
0
8
2
Order By: Relevance
“…These findings are analogous to those of Herzallah et al, 12 who reported RMCs being present in 79.4% of CTs of sinuses, with 50.3% harboring mucosal disease among patients with revision FESS. However, the current study yielded findings different from those reported by Chapurin et al, 13 who found RMCs in only 16% of CTs of sinuses but that 74% contained diseased mucosa. It is worth mentioning, however, that Chapurin et al 13 uses a somewhat different definition of RMCs (i.e., contained within the posterior maxillary sinus), which may explain the differences in prevalence.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings are analogous to those of Herzallah et al, 12 who reported RMCs being present in 79.4% of CTs of sinuses, with 50.3% harboring mucosal disease among patients with revision FESS. However, the current study yielded findings different from those reported by Chapurin et al, 13 who found RMCs in only 16% of CTs of sinuses but that 74% contained diseased mucosa. It is worth mentioning, however, that Chapurin et al 13 uses a somewhat different definition of RMCs (i.e., contained within the posterior maxillary sinus), which may explain the differences in prevalence.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the current study yielded findings different from those reported by Chapurin et al, 13 who found RMCs in only 16% of CTs of sinuses but that 74% contained diseased mucosa. It is worth mentioning, however, that Chapurin et al 13 uses a somewhat different definition of RMCs (i.e., contained within the posterior maxillary sinus), which may explain the differences in prevalence. No patients had isolated RMC disease, and all who required revision FESS in this study had other causes for failure (e.g., pansinusitis, recurrent disease, failure of other sinuses), which indicated that RMC disease, expectedly, is more likely to occur in the more common setting of multiple diseased sinuses, and it would be rare to have isolated opacification of the RMCs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Liu et al 16 analyzed 103 sinus CTs and found that the incidence of RMC was 74.30%. Chapurin et al 17 indicated that the incidence of RMC was 16%, but the CT pictures provided in his paper show the EMS. The difference may be due to the ethnicities, the number of samples, and the different criteria of identifying the RMC.…”
Section: Discussionmentioning
confidence: 91%
“…To our knowledge, few studies about RMC have been reported. [14][15][16][17] The exact anatomic characteristics was still unclear and it is often confused to some other anatomical structure that is located between the MS and orbit such as EMS, Haler cell, and anterior extension of the sphenoid sinus. The distinction of EMS and RMC is ambiguous and vague particularly.…”
Section: Introductionmentioning
confidence: 99%